Entrepreneurial Characteristics and Entrepreneurial Intention: The Mediating Role of Entrepreneurial Mindset - Nemino, Rommel (International Journal of Business, Management and Economics, 2025)
ABSTRACT: This study aims at examining the relationship between entrepreneurial characteristics and entrepreneurial intention as well as the mediating role of entrepreneurial mindset among university students. Descriptive correlational technique to conduct non-experimental quantitative research approach was utilized to provide a detailed understanding of the influence among the constructs. This study involved 385 fourth-year Bachelor of Science in Hospitality Management (BSHM) and Bachelor of Science in Business Administration (BSBA) students majoring in Financial Management (FM) and Human Resource Management (HRM) who enrolled in entrepreneurship courses. The result reveals that entrepreneurial characteristics have a significant positive effect on entrepreneurial intention. Additionally, direct and indirect models show that entrepreneurial mindset mediates the relationship between entrepreneurial characteristics and entrepreneurial intention. This suggest that entrepreneurial characteristics such as locus of control, need for achievement, risk-taking propensity, innovativeness, self-efficacy, and tolerance to ambiguity are important drivers of entrepreneurial intention, with entrepreneurial mindset that will acts as a catalyst that translates these characteristics to intentions. This study highlights the importance of cultivating entrepreneurial mindset in higher education to bridge the gap between inherent traits and actual entrepreneurial pursuits, which is in accordance with the fourth and eight sustainable development goals which indicates quality education, decent work and economic growth. Future investigations are encouraged to explore additional variables and conduct longitudinal studies to provide a deeper understanding of this dynamic.